PENGGUNAAN KANBAN DALAM METODE JUST IN TIME PADA PRODUKSI - Achmadi, Hendra (CommIT (Communication and Information Technology) Journal, 2008)
Competition among textile companies is very heavy, especially when dealing with the WTC event in America. This caused a hard shock for the textile companies in Indonesia because many textile companies must divert their focus to local market. As we know, if most of textile companies divert their attention to domestic market, the next problem will happen is more companies entering to local or domestic market, so that more increasing the competition among textile companies. Competition occurs is price competition so that textile companies must continuously introspect themselves so they can compete, and the next is time. In an increasingly competitive world now caused it needs a new breakthrough, in time of samples creating and also textile production itself. The production amount resulted per day is large so that it must be absorbed by market. They can be marketed through a hypermarket or a traditional market. Therefore, the use of information technology is very useful for winning the competition among textile mill. Because the work of the textile industry also must obtain a new order that is done, it needs to make an existing production model of the new order (Just In Time); made to reduce the amount of stock that is stored, it will follow the Japanese style, which is called the Kanban system. In this system, the new company will produce if there is order.Keywords: kanban, textiles, just in time